2009
DOI: 10.1243/09576509jpe826
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental investigation of a low-pressure steam turbine during windage

Abstract: Modern steam power plants must operate safely at extremely low loads, known as windage, in which the low pressure (LP) turbine runs with decreased or even zero flow. Windage is characterized by a strongly unsteady three-dimensional (3D) flow field leading to possible aerodynamic excitations. Extensive flow field measurements were performed in an LP steam turbine test rig during windage, using pneumatic probes in the last stage and a diffuser. The flow field of the whole turbine was also calculated with steady … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 8 publications
3
23
0
1
Order By: Relevance
“…While most authors investigating flow effects during very low volume flow have tended to use single passage, multistage calculations [5,12], the authors are not aware of a reported study indicating the sensitivity of the blade temperature prediction to the CFD setup. To address this, a number of sensitivity studies were conducted in order to ascertain the most suitable CFD setup to predict the LSB temperature for the required degree of accuracy.…”
Section: Cfd Modeling Of Blade Temperaturesmentioning
confidence: 99%
See 4 more Smart Citations
“…While most authors investigating flow effects during very low volume flow have tended to use single passage, multistage calculations [5,12], the authors are not aware of a reported study indicating the sensitivity of the blade temperature prediction to the CFD setup. To address this, a number of sensitivity studies were conducted in order to ascertain the most suitable CFD setup to predict the LSB temperature for the required degree of accuracy.…”
Section: Cfd Modeling Of Blade Temperaturesmentioning
confidence: 99%
“…Figure 21 shows the measurement blade temperatures and the spanwise distribution of maximum blade temperatures found along each span line up the blade. It is clear there is little sensitivity to running a steady state or transient full annulus calculations (cases [4][5][6] or if the unsteady SAS turbulence model is used (case 6). This supports the results of the temperature deltas in Fig.…”
Section: Comparison Of Cfd and Measurement Datamentioning
confidence: 99%
See 3 more Smart Citations